2011
DOI: 10.5550/sgia.110702.en.113c
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Biomechanical Parameters in the Triple Jump Technique – A Case Study

Abstract: The purpose of the study was to examine consistency and variability of kinematical parameters in the triple jump technique. An analysis has been carried out on the basis of two attempts of a female athlete who is one of the best triple jumpers in the world. The latest biomechanical technology and the methodology of measurements in the triple jump have been used. The Opto-track technology and 3-D kinematical technology were used in order to analyse parameters of the model technique in the triple jump. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that there is a significant positive relationship between and horizontal velocity during sprint running [01,10,15,01,24 ], long distance running [19] and treadmill running [18 ],and a significant negative relationship between and loss of horizontal velocity during repeated sprinting [10 ].However some previous studies demonstrated that there is no significant relationship between and horizontal velocity during sprint, treadmill and distance running [8,9,18,01,24]. previous studies on triple jump focused mainly either on kinematical analysis of the individual athlete techniques [12,14 ,17], Ground reaction forces during three take off actions [7,13] or more specific aspects of the optimum phase ratio [4,17] but until now no studies focus on changes in spring mass model characteristics during triple jump Figure (1) the model consists of a mass and a single leg spring (which joins the foot and the center of mass DL is its maximal compression. ( ) is the vertical displacement of the mass during the stance phase, and (∆L) is the vertical compression of the leg spring during the mid-stance phase [6] So the main aim of the present study to identify changes in vertical and leg stiffness during triple jump and identify the relationship between both vertical and leg stiffness and horizontal velocity and the loss of horizontal velocity during triple jump performance.…”
Section: Vertical Stiffness (mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that there is a significant positive relationship between and horizontal velocity during sprint running [01,10,15,01,24 ], long distance running [19] and treadmill running [18 ],and a significant negative relationship between and loss of horizontal velocity during repeated sprinting [10 ].However some previous studies demonstrated that there is no significant relationship between and horizontal velocity during sprint, treadmill and distance running [8,9,18,01,24]. previous studies on triple jump focused mainly either on kinematical analysis of the individual athlete techniques [12,14 ,17], Ground reaction forces during three take off actions [7,13] or more specific aspects of the optimum phase ratio [4,17] but until now no studies focus on changes in spring mass model characteristics during triple jump Figure (1) the model consists of a mass and a single leg spring (which joins the foot and the center of mass DL is its maximal compression. ( ) is the vertical displacement of the mass during the stance phase, and (∆L) is the vertical compression of the leg spring during the mid-stance phase [6] So the main aim of the present study to identify changes in vertical and leg stiffness during triple jump and identify the relationship between both vertical and leg stiffness and horizontal velocity and the loss of horizontal velocity during triple jump performance.…”
Section: Vertical Stiffness (mentioning
confidence: 99%
“…From the biomechanical aspect, triple jump is one of the most complex track and field disciplines and consists of the run-up phase and three consecutive flight phases which are hope, step and jump [17].An elite triple jumper should be able to reach average speeds of more than 10.4 m´s-1during the last 5 m before the take-off, and to maintain as much of this speed as possible during the hop, the step and the jump [22]. This is possible only by minimizing the braking forces, thus optimizing vertical velocity.…”
mentioning
confidence: 99%
“…Earlier biomechanical studies of the triple jump focused mainly on qualitative comparisons of the triple jump techniques for individual athletes [2,6,7] or some more specific analyses like the optimum phase ratio [3,6,8], functions of arm swing motions [2,9], tradeoffs between velocity components during triple jumping [10], and biomechanical loading [4,11]. The present paper attempts to supplement these studies with the inverse dynamics analysis of the triple jump, based on musculoskeletal modeling and computer simulations, and aimed at quantitative evaluation of the lower-limb muscle forces and joint reaction forces during the movement.…”
mentioning
confidence: 99%